Process for Settlement of Criminal Road Traffic Accidents Through Mediation - Juhari Juhari; Kastubi Kastubi (International Forum of Researchers and Lecturers, 2023)
A road traffic accident is an unexpected and unintentional event on the road involving a vehicle with or without other road users which results in loss and/or loss of property. If the violation gives rise to criminal consequences attached to the violation, then the violation is a criminal offense. Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation, regulates lex specialis, regarding the process of resolving cases of criminal traffic accidents, However, the resolution of this case is also often carried out outside of court or in other words it is resolved through peace (islah) between the parties, this mechanism is often also called Alternative Dispute Resolution (ADR). Handling criminal cases that occur in society can be resolved using two methods, namely penal and non-penal. One of the non-penal solutions is Penal Mediation. Penal mediation itself is born from the culture that exists in society so that the content of its values is in accordance with the characteristics of the Indonesian nation. Mediation is a procedure based on